Optimum and Green Fabrication of MIL-100(Fe) for Crystal Violet Dye Removal from Aqueous Solution - Wijaya, Christian Julius; Soetaredjo, Felycia Edi; Yuliana, Maria; Santoso, Shella Permatasari; Hartono, Sandy Budi; Irawaty, Wenny; Lie, Jenni; Putro, Jindrayani Nyoo; Gunarto, Chintya; Puspitasari, Nathania; Ismadji, Suryadi; Gunawan, Setiyo (Universitas Gadjah Mada, 2024)
MIL-100(Fe) was prepared and subsequently used to remove crystal violet dye from aqueous solutions simulating dye-containing wastewater in the environment. In the future, it is aimed that MIL-100(Fe) can be used in managing dye-containing wastewater in the environment and reducing the negative impacts it can cause. Here, MIL-100(Fe) fabrication needs to be optimized to obtain optimum process conditions, which are environmentally friendly and can produce MIL-100(Fe) with the best characteristics. This study focused on optimizing the fabrication of MIL-100(Fe), which is a type of MOF with good chemical stability, thermal stability, and flexible structure. In this study, the room-temperature fabrication of MIL-100(Fe) was established using a ligand-to-metal molar ratio of 0.95 and an acetic acid concentration of 5.1 vol% for 6.2 h. The optimum MIL-100(Fe) was tested for crystal violet removal and provided an optimum removal capacity of 182.66 ± 3.81 mg/g. Statistical approaches are used to investigate the independent parameters and their interactions contributing to MIL-100(Fe) formation.